Zora and me. The summoner - Bond, Victoria, 1979- (Candlewick Press, 2020)
Carrie and her best friend, Zora--who will go on to become the famous Zora Neal Hurston--find themselves having to grow up fast when a lynch mob crosses into their idyllic, all-black township of Eatonville. Then, a grave robbery brings to light secrets from the town's past trespasses and sets the town's first and only mayor against the charismatic preacher, who happens to be Reverend John Hurston, Zora's father. Finally, after all these struggles, Zora recognizes a life change is coming, and she and Carrie will have to leave Eatonville behind.